Clinical, laboratory and ultrasonographic correlation in assessing severity and outcome in dengue infection - Chapala, Pallavi; Penubolu, Kiranmayee; Venkata Soujanya, Rajamanuri; Narasimha Rao, S. (International Journal of Contemporary Pediatrics, 2026)
Background: Dengue infection is a major public health concern with clinical manifestations ranging from mild febrile illness to life-threatening shock syndrome. Early prediction of disease progression is vital for reducing morbidity and mortality. This study aimed to document the clinical profile of pediatric patients and evaluate the correlation of liver enzymes, viral serotypes, and abdominal ultrasonographic findings with the severity and outcome of dengue infection. Methods: A prospective observational study was conducted over a period of 20 months involving 65 children (n=65) aged 1 month to 18 years admitted with confirmed dengue infection. Clinical features, liver function tests (AST, ALT, ALP), serotypes and abdominal ultrasound findings were analyzed. Statistical analysis was used to correlate these findings with disease severity. Results: The majority of the study population were males (58.46%) with the highest incidence in the 1–5 year age group (35.38%). Fever was universally present, while hepatomegaly was observed in 20% of cases. DENV-2 was the predominant serotype (49.23%). Significant statistical differences were noted in Alkaline Phosphatase (ALP) and alanine transaminase (ALT) levels among different serotypes (p<0.05). Ultrasonography revealed warning signs such as ascites (36.9%) and gall bladder edema (30.7%). A statistically significant association was found between dengue severity and ultrasound warning signs (p<0.0000001), with an area under the ROC curve of 0.96. Conclusions: Ultrasound warning signs are strong predictors of dengue severity in children. While liver enzyme levels vary significantly by serotype, abdominal ultrasonography serves as a highly sensitive and reliable non-invasive tool for the early prediction of severe dengue infection and timely management of pediatric dengue patients.